Gallbladder Kinetics: Correlation between Gall Bladder Emptying in Patients With and Without Cholelithiasis by Ultrasonography - Jaiswal, P; Sharma, P; Shrestha, DM; Pradhan, S (Nepalese Journal of Radiology, 2012)
Background: Gallstone disease or cholelithiasis, is one of the most common surgical problems worldwide. The assessment of gallbladder kinetics in patients with cholelithiasis as well as in patients with high risk for cholelithiasis could play a significant role in better management and is recommended as a routine workup of biliary system in these patients. Objectives: This study was carried out to establish the relationship between impaired gall bladder emptying and gall bladder stones. It also aimed at finding out correlation between chosen risk factors. Materials and Methods: Eighty six subjects with cholelithiasis and 35 controls (without cholelithiasis) were studied. Pre-prandial gall bladder volume was measured after 6 hours of fasting, gallbladder emptying was stimulated by fatty meals of 610 and 740Kcal and post-prandial gallbladder volume was measured after a period of two hours with ultrasound. The difference of pre-prandial and postprandial gall bladder volume was calculated. Results: Gallbladder emptying was significantly more (p < 0.001) in the control group than in the group of subjects with cholelithiasis. In the case group the mean difference of volume was 9.2±7.1 cc. While in control group the mean difference of volume was 17.6±14.3. The prevalence of cholelithiasis was significantly high in females between 26- 35 years of age group and in patients with nonalcoholic fatty liver disease and in patients who had first degree relative with gall stone. Incidence of silent gall stone was also statistically significant. Conclusion: Impaired gallbladder emptying was found to be strongly associated with gall stones. NJR I VOL 2 I ISSUE 1 13-17 Jan-June, 2012 DOI: http://dx.doi.org/10.3126/njr.v2i1.6973